Specific inspiratory muscle warm-up enhances badminton footwork performance - Lin, H.; Kwokkeung Tong, T.; Huang, C.; Nie, J.; Lu, K.; Quach, B. (Applied Physiology, Nutrition, and Metabolism, 2007)
The effects of inspiratory muscle (IM) warm-up on IM function and on the maximum distance covered in a subsequent incremental badminton-footwork test (FWmax) were examined. Ten male badminton players were recruited to perform identical tests in three different trials in a random order. The control trial did not involve an IM warm-up, whereas the placebo and experimental trials did involve an IM warm-up consisting of two sets of 30-breath manoeuvres with an inspiratory pressure-threshold load equivalent to 15% (PLA) and 40% (IMW) maximum inspiratory mouth pressure, respectively. In the IMW trial, IM function was improved with 7.8% ± 4.0% and 6.9% ± 3.5% increases from control found in maximal inspiratory pressure at zero flow (P0) and maximal rate of P0 development (MRPD), respectively (p < 0.05). FWmax was enhanced 6.8% ± 3.7%, whereas the slope of the linear relationship of the increase in the rating of perceived breathlessness for every minute (RPB/min) was reduced (p < 0.05). Reduction in blood lactate ([La-]b) accumulation was observed when the test duration was identical to that of the control trial (P < 0.05). In the PLA trial, no parameter was changed from control. For the changes (Delta) in parameters in IMW (n = 10), negative correlations were found between DeltaP0 and DeltaRPB/min (r2 = 0.58), DeltaMRPD and DeltaRPB/min (r2 = 0.48), DELTARPB/min, and DeltaFWmax (r2 = 0.55), but not between Delta[La-]b accumulation and DeltaFWmax. Such findings suggest that the IM-specific warm-up improved footwork performance in the subsequent maximum incremental badminton-footwork test. The improved footwork was partly attributable to the reduced breathless sensation resulting from the enhanced IM function, whereas the contribution of the concomitant reduction in [La-]b accumulation was relatively minor.